Peran Muslimat NU dalam Pemberdayaan Perempuan (Studi kasus: Muslimat NU Desa Tuwel Kabupaten Tegal) - Arofah, Nur; ., Kushandajani (Journal of Politic and Government Studies, 2018)
As the under bow of one of the biggest socio-religious organizations in Indonesia, Muslimat NU has a great potential to empower women, specifically a village society. Unfortunately, the fact is Muslimat NU empowerment is still in religious literacy level, which is recitation. Besides, the strengthening of religious literacy through recitation, Muslimat NU of Tuwel village also has a number of empowerment activities aim at strengthening the economy and environment, such as goods credits, kube, and Rubbish bank.This research aims to analyze women empowerment process in Tuwel Village, Tegal Regency, including the implications of women empowerment by Muslimat NU of Tuwel Village in various aspects, that are economic, social and politics. The researcher used qualitative method by using observation and in-depth interview as data collection technique. Result of the study indicates that Muslimat NU of Tuwel Village empowerment relies on the board of low section (anak ranting) or people call by jamiyah or majelis ta’lim. Muslimat NU of Tuwel Village is recognized as active since long time ago, through Recitation activity and a series of social activities, but non-religious activities are pioneered around the last 7 years from 2011.Muslimat NU of Tuwel Village is supported by many resources, ranging from internalization of high religious value, economic ability, and cooperation relationship with other agencies that has been running well. For the sense of agency associated with power relation, it has started from some members. The empowerment impact is still largely at the level of gender practical needs fulfillment. From result of the study it can be concluded that Muslimat NU of Tuwel Village empowerment is limited on empowerment to fulfill gender practical needs, yet this empowerment began to lead to the strategic empowerment, in which women's participation in the establishment is started be involved, beside, male awareness in mainstreaming gender starts to increase.Keywords: Women, Empowerment, Muslimat NU